(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
Bioremediation of soil pollutants, such as glyphosate, is a cost-effective and ecologically sustainable method. Glyphosate, a highly prevalent herbicide utilized for weed control, presents substantial hazards to species and their ecosystems when it becomes present in the environment. The objective of this study was to investigate the ability of a Pseudomonas sp. isolated from a coastal area. The isolate with the highest potential was provisionally identified as Pseudomonas sp. strain Andalas2016 using partial identification techniques. This bacterium shows substantial capacity for glyphosate breakdown under ideal circumstances. The experiments revealed that Pseudomonas sp. exhibits optimal degradation of glyphosate under the following conditions: pH 7.0, glyphosate concentration of 0.5 g/L and temperatures ranging from 30 to 35°C. The bacterium had a delay of two days when exposed to 0.5 g/L glyphosate but achieved about 90% degradation after six days of incubation. Bacterial growth was significantly reduced by heavy metals, namely Hg(II), Ag(I), and Cu(II). Growth on glyphosate was inhibited at salinity higher than seawater level. This study highlights the capacity of Pseudomonas sp. to remediate glyphosate-contaminated settings through bioremediation. It emphasizes the necessity for additional investigation, specifically using molecular identification techniques, to thoroughly understand and enhance this bioremediation approach. This strategy has the potential to greatly reduce the environmental effects of glyphosate pollution, while also supporting the development of healthier environments and environmentally friendly farming methods.